Bargaining Power of Buyersâ€™ Collectivism to Enhance Sustainability Development - Eugene, Hakizimana; Becerril, Dulce María Monroy; Muñoz-Sánchez, Christian; Díaz, Esteban Martínez (Fronteira: Journal of Social, Technological and Environmental Science, 2025)
M. Porter in his model shows how consumers bargaining power contributes to industrial competition by helping to achieve provision of higher quality products, better customer services, and lower prices benefits. However, according to Lowitt and Tylenda, these benefits are factors of sustainability development which is a current concern of consumers. This paper tries to close this gap of not only considering bargaining power as a tool for competitive strategy but also to study how responsible consumers collectively enhance sustainability development. To achieve this objective, integrative review method and European green deal data of Eurostat sustainable development indicators were used. Research results are according to literature review, bargaining power of customers enhance sustainability achievement through provision of competitive benefits, and this is done in collective means. This is supported by European Union sustainability indicators by which, a significant relation of customers forces, and sustainability development indicators were identified.